مسؤولية رئيس مجلس النواب في دستور جمهورية العراق لعام 2005: دراسة مقارنة - طالب مصدق عادل; خلف فاروق عز الدين (Journal of Legal Sciences, 2019)
This research deals with the responsibility of the President of the House of Representatives in the Constitution of the Republic of Iraq for the year 2005 and comparative constitutions as it considered the leader of the legislative authority. Therefore we research the types of this responsibility, explain the boundaries in exercised it, so in relation to the dismissal or impeachment or disciplinary responsibility, whether to identify the reasons of responsibility or its competence authority to impose, and procedures should be followed.